Induction of the Mitochondrial Permeability Transition in Vitro by Short-Chain Carboxylic Acids - Palmeira, C. M. (2000)
We recently reported that acrylic acid (AA) induces the MPT in vitro, which we suggested might be a critical event in the acute inflammatory and hyperplastic response of the olfactory epithelium. The purpose of the present investigation was to determine if induction of the MPT is a general response to short-chain carboxylic acids or if there are critical physical chemical parameters for this response. Freshly isolated rat liver mitochondria were incubated in the presence of varying concentrations of selected carboxylic acids. All of the acids that we tested caused a concentration-dependent induction of the MPT, which was blocked by cyclosporine A. Although the C4 carboxylic acids were slightly more potent than the C5 acids, there was no correlation with the degree of saturation, the octanol/water coefficient (log P), or the dissociation constant (pKa) of the acids that we tested. We conclude that induction of the MPT in vitro is a general response to short-chain carboxylic acids having a pKa of 4 to 5.